СИБИРСКОЕ КНИГОИЗДАНИЕ В КОНЦЕ XX - НАЧАЛЕ XXI в. (Библиосфера, 2010)
The article discusses the structure of the book-publishing system in Siberia in the post-Soviet development. An attempt is maid to reveal the dynamics of the Siberian publishing, to show the role of government, institutional and private publishers in today's book publishing in Siberia.